2015
DOI: 10.24841/fa.v24i2.78
|View full text |Cite
|
Sign up to set email alerts
|

AS ESPÉCIES DE COPEPODA (CRUSTACEA: ERGASILIDAE) PARASITAS DOS FILAMENTOS BRANQUIAIS DE Potamorhina latior (Spix & Agassiz, 1829) (CHARACIFORMES: CURIMATIDAE) DE LAGOS DE VÁRZEA DA AMAZÔNIA CENTRAL, BRASIL

Abstract: RESUMO THE SPECIES OF COPEPODA (CRUSTACEA: ERGASILIDAE) PARASITES OF GILL FILAMENTS OF Potamorhina latior (Spix & Agassiz, 1829) (CHARACIFORMES: CURIMATIDAE) OF CENTRAL AMAZON FLOODPLAIN LAKES, BRAZIL ABSTRACTThree species of Copepoda were collected in the gills of Potamorhina latior from six floodplain lakes, five from Solimões River and one from the Purus River, Amazonas State: Amplexibranchius bryconis; Ergasilus jaraquensis and Miracetyma etimaruya. Potamorhina latior is a new host for A. bryconis and E. j… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Gomes (2018) also identified these copepods in M. duriventre collected in floodplain lakes in the Solimões River. Other studies involving different hosts have also reported parasitism by A. bryconis in fish from the floodplains of the Negro, Solimões and Purus rivers (Dumbo, 2014;Morey et al, 2015;Morey, 2017;Vital, 2018).…”
Section: /11mentioning
confidence: 89%
“…Gomes (2018) also identified these copepods in M. duriventre collected in floodplain lakes in the Solimões River. Other studies involving different hosts have also reported parasitism by A. bryconis in fish from the floodplains of the Negro, Solimões and Purus rivers (Dumbo, 2014;Morey et al, 2015;Morey, 2017;Vital, 2018).…”
Section: /11mentioning
confidence: 89%